2018
DOI: 10.1177/1747021818791079
|View full text |Cite
|
Sign up to set email alerts
|

Saving the Perruchet effect: A role for the strength of the association in associative learning

Abstract: In a partial reinforcement schedule where a cue repeatedly predicts the occurrence of a target in consecutive trials, reaction times to the target tend to decrease in a monotonic fashion, while participants' expectancies for the target decrease at the same time. This dissociation between reaction times and expectancies-the so-called Perruchet effect-challenges the propositional view of learning, which posits that human conditioned responses result from conscious inferences about the relationships between event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
2
1
Order By: Relevance
“…However, in a recent study, we showed that performance in the Perruchet task does not only reflect associative strength (Destrebecqz et al, 2019). Our results demonstrated an additional influence of expectancies on performance.…”
contrasting
confidence: 39%
“…However, in a recent study, we showed that performance in the Perruchet task does not only reflect associative strength (Destrebecqz et al, 2019). Our results demonstrated an additional influence of expectancies on performance.…”
contrasting
confidence: 39%
“…In a recent study, we further demonstrated that the Perruchet dissociation in the cued RT task cannot be attributed to non-associative factors such as a decrease in vigilance or a mere motor priming (Destrebecqz et al 2019). We instead observed a small but reliable infl uence of the strength of the tone-target association on participants' performance when these potential non-associative confounds were controlled for.…”
Section: E Perruchet E Ectmentioning
confidence: 49%
“…That is, the conditioned response (blinking) and conscious expectancy went in opposite directions (see e.g. Destrebecqz et al, 2019, for evidence that the Perruchet effect as shown in a reaction time paradigm involves a dissociation between expectations and associative processes). The conditioned response therefore plausibly reflects unconscious structural learning.…”
Section: Conscious Versus Unconscious Learningmentioning
confidence: 99%